The Mind Game: Invisible Cheating and Inferable Intentions - Ting Jiang (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
This paper exploits a novel cheating game - the ?Mind Game? - to show how a subtle variation in the rules of the game affects cheating. In both variants of the game, cheating is invisible because subjects make their choices purely in their minds. The only difference rests on the order of the steps in which subjects should play the game. I find that subjects cheat significantly less when they have to disregard the prescribed order of steps in order to cheat, compare to when they can purely lie about the choice made in the mind. Since subjects play the game in private with a double-blind payment procedure, I conjecture that subjects only cheat to the extent that their moral self-image is still preserved. But the moral image can be preserved if they can deceive themselves into believing that at least their intentions are good, and not if cheating requires an act that reveals the intent to cheat. This study thus suggests a potential role of intent inference in deterring cheating.
Keywords: C91; D63; H26; K42; 330; cheating; intent; self-deception; moral self-image; the mind game